OPTIMIZATION OF LEARNING MEDIA IN HIGHER EDUCATION IN METRO CITY - Isti Fatonah; Rafiud Ilmudilulloh; Alvin Firman Fauzan; Maulinda Amalia Hafifah; Nurlia Puji Utami (Ri'ayah: Jurnal Sosial dan Keagamaan, 2023)
Learning media in tertiary institutions have many obstacles in their use. One of them is the application of learning, learning strategies, learning media, and teaching resources. These are some of the external elements that contribute to learning problems. This study aims to find out how the efforts to optimize learning media in Metro City tertiary institutions. This research is a type of field research with a qualitative approach. Collecting data using the method of observation, interviews, and documentation. The results of learning media research at several universities in Metro City have developed quite a bit, although there are still universities whose learning media are not optimal. So that the teaching and learning process carried out by lecturers and students becomes hampered.